2013
DOI: 10.1088/0004-637x/763/1/60
|View full text |Cite
|
Sign up to set email alerts
|

A Sample of Seyfert-2 Galaxies With Ultraluminous Galaxy-Wide Narrow-Line Regions: Quasar Light Echoes?

Abstract: We report the discovery of Seyfert-2 galaxies in SDSS-DR8 with galaxy-wide, ultra-luminous narrow-line regions (NLRs) at redshifts z = 0.2 − 0.6. With a space density of 4.4 Gpc −3 at z ∼ 0.3, these "Green Beans" (GBs) are amongst the rarest objects in the Universe. We are witnessing an exceptional and/or short-lived phenomenon in the life cycle of AGN. The main focus of this paper is on a detailed analysis of the GB prototype galaxy J2240-0927 (z = 0.326). Its NLR extends over 26×44 kpc and is surrounded by a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(121 citation statements)
references
References 91 publications
15
106
0
Order By: Relevance
“…We have pursued detailed study of this subset of 8 (plus IC 2497/Hanny's Voorwerp) to learn more about AGN variations on the otherwise inaccessible range of time scales 10 4 − 10 5 years. Analogous cases of extended ionized gas near energetically inadequate AGN have been reported at higher redshift and luminosity by Schirmer et al (2013) and Schirmer et al (2016), their "Green Bean" systems, and at low luminosity in the local Universe in the merger remnant NGC 7252 (Schweizer et al 2013) and as one interpretation of an off-nuclear ionized region in the spiral galaxy NGC 3621 (Menezes et al 2016).…”
Section: Introductionsupporting
confidence: 56%
“…We have pursued detailed study of this subset of 8 (plus IC 2497/Hanny's Voorwerp) to learn more about AGN variations on the otherwise inaccessible range of time scales 10 4 − 10 5 years. Analogous cases of extended ionized gas near energetically inadequate AGN have been reported at higher redshift and luminosity by Schirmer et al (2013) and Schirmer et al (2016), their "Green Bean" systems, and at low luminosity in the local Universe in the merger remnant NGC 7252 (Schweizer et al 2013) and as one interpretation of an off-nuclear ionized region in the spiral galaxy NGC 3621 (Menezes et al 2016).…”
Section: Introductionsupporting
confidence: 56%
“…More problematic could be the challenge of measuring some of these lines. For example, [Ne iii]λ3343 can potentially be blended with the [Ne v]λ3347 line (Schirmer et al 2013), while Si ii λ1814 has been found to be very weak in high-redshift quasars (Negrete et al 2014). …”
Section: Ne-based Diagnostics In the Near Ultravioletmentioning
confidence: 99%
“…The host is most likely a rare green bean galaxy (GBG; Schirmer et al 2013). The GBGs are extended objects (Petrosian radius r 2 Petro > ) and have g r 1.0 -> .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…17 Petro =    , and with colors g r 1.02 0.04 -=  , r i 0.06 0.03 -=  , u r 2.36 0.20 -=  , and r z 0.57 0.05 -=  it is located in the region occupied by galaxies in Figure 2 of Cardamone et al (2009), outside the selection requirement for green bean galaxies. The host colors meet 11 of 12 selection criteria for selection of GBGs proposed by Schirmer et al (2013). We discuss this further in Section 4.2.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation